“Application of Competency-Based and Digital Approaches to Enhance Physical Education Teacher Training in Higher Education” - Musayev Otabek Qudratovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article investigates the application of competency-based and digital approaches in enhancing the training of physical education teachers in higher education. The study emphasizes the integration of theoretical knowledge, practical skills, and reflective practices to improve professional competencies. It examines the role of digital learning technologies, interactive methods, and competency-based strategies in optimizing lesson quality, promoting active student engagement, and supporting holistic student development. The paper also provides recommendations for effective implementation of these approaches in teacher training programs.